Looking in on music: Challenges and opportunities for the Scholarship of Teaching and Learning - Conkling, Susan Wharton (Teaching and Learning Inquiry, 2016)
Whereas most articles in this special issue demonstrate careful and close-up views of Scholarship of Teaching and Learning (SoTL) in a performing arts or humanities discipline, my approach is opposite; I look in on music teaching and learning to interrogate current conceptions of SoTL. I begin with Sloboda’s cognitive explanation of music expertise and consider how music expertise is established relatively early in life. I then proceed to develop two case studies of music in higher education showing how each case illustrates expertise, and highlighting experts’ desires for progressively greater challenges. I argue that collaboration with other expert performers is one sort of challenge that meets such desires. By drawing attention to collaboration, I then reframe music as social practice, and I highlight the qualities of participatory performance. In the latter part of the article, I turn my attention toward explaining what it means to think about learning as participation in a community of practice, and I draw on the case studies to demonstrate that such a view presents both challenges and opportunities for SoTL.